Classroom Dynamics in the Foreign Language Classroom - Bohara, Lal Bahadur (Spandan, 2018)
To have the purpose for exploring the classroom dynamics of foreign language teachers and students, the researcher had conducted the comprehensive field study. Both teachers and students are supposed as the individually different personalities with respect to their sociocultural background, behaviors, interests, attitudes and so forth. Well consideration of classroom context and culture might ensure the betterment of the students. It might be more essential in the rural classroom where the situation of foreign language teaching is said to be challengeable. For this research study, 2 teachers and 10 students were selected purposively. Later on, the information was collected through in-depth interview and class observation; and analyzed them after all. After the analysis and interpretation of the information, it was found that because of being the teachers demotivated, the classroom dynamics had been poorly understood and exercised, consequently, the students were disappointed. Hopefully, the finding might be helpful for foreign language teachers, teacher-educators, school supervisors and students as well.